Prominent Agroforestry Systems Adopted by Farmers in Seoni District of Madhya Pradesh - Berry, Nanita; Dilraj, Itk; Dubey, Sourabh; Rai, Nikita (Indian Forester, 2023)
An extensive field survey was conducted to assess the impact of adoption of agroforestry system adopted by the farmers in Seoni district which comes under Kymore plateau and Satpura Hills agro climatic zone of Madhya Pradesh. Information like tree and crop species combinations, reason for adoption, challenges faced by farmers, source of Quality Planting Material, planting pattern and other relevant parameters were collected from the farmers by conducting personal interview with pre-tested questionnaire during 2019-2020. The study revealed that farmers have adopted silvi-agri-horti (48.85%), silvi-agri (28.85%), horti-agri system (20%) etc. It was found that maximum farmers preferred Tectona grandis under silvi-agri system while Mangifera indica in silvi-horti-agri and horti-agri systems. Majority of farmers (50.57%) preferred bund plantation. Choice of tree-crop, tree planting pattern mainly depends upon size of landholding, knowledge of agroforestry and soil type etc also affects adoption of by them tree farming.